Investigations into the initial composition of latent fingermark lipids by gas chromatography-mass spectrometry - Frick, Amanda; Chidlow, Geoff; Lewis, Simon; Van Bronswijk, Wilhelm (Elsevier Ireland Ltd, 2015)
A more comprehensive understanding of the variability of latent fingermark composition is essential to improving current fingermark detection capabilities in an informed manner. Gas chromatography–mass spectrometry was used to examine the composition of the lipid fraction of latent fingermarks collected from a population of over 100 donors. Variations in the appearances of chromatograms from different donors were apparent in the relative peak sizes of compounds including free fatty acids, squalene, cholesterol and wax esters. Principal component analysis was used as an exploratory tool to explore patterns in this variation, but no correlation to donor traits could be discerned. This study also highlights the practical and inherent difficulties in collecting reproducible samples.